Template matching to support earth observation based refugee camp analysis in obia workflows : creation and evaluation of a dwelling template library for improving dwelling extraction within an object-based framework - Krafft, P. (2020)
Accurate and reliable information about the situation in refugee or internally displaced person camps is very important for planning any kind of help like health care, infrastructure or vaccination campaigns. The number and spatial distribution of single dwellings extracted semi-automatically from very high resolution (VHR) satellite imagery as an indicator for population estimations can provide such important information. The accuracy of the extracted dwellings can vary quite a lot depending on various factors. To enhance established single dwelling extraction approaches, we have tested the integration of stratified template matching methods in objectbased image analysis (OBIA) workflows. The created template library aims to be generally applicable in similar conditions. Compared to pre-existing OBIA classifications, the approach could increase in average the producer’s accuracy by 12% and also slightly increase the user’s accuracy. These results show that the stratified integration of template matching approaches in OBIA workflows is a possibility to further improve results of semi-automated dwelling extraction, especially in complex situations.boundaries.